Walking a fine line: is it possible to remain an empathic physician and have a hardened heart? - Newton, Bruce W. (Frontiers in Human Neuroscience, 2013)
Establishing an empathic physician-patient relationship is an essential physician skill. This chapter discusses the sexually dimorphic aspects of the neural components involved in affective and cognitive empathy, and examines why men and women medical students or physicians express different levels of empathy. Studies reveal levels of medical student affective or cognitive empathy can help reveal which medical specialty a student will enter. The data show students or physicians with higher empathy enter into specialties characterized by large amounts of patient contact and continuity of care; and individuals with lower levels of empathy desire specialties having little or no patient contact and little to no continuity of care. Burnout and stress can decrease the empathy physicians had when they first entered medical school to unacceptable levels. Conversely, having a too empathetic physician can let patient conditions and reactions interfere with the ability to provide effective care. By learning to blunt affective empathic responses, physicians establish a certain degree of empathic detachment with the patient in order to provide objective care. However, a physician must not become so detached and hardened that their conduct appears callous, because it is still important for physicians, especially those in specialties with a large amount of patient contact, to use empathic communication skills.